Embodied health practices:The use of Traditional Healing and Conventional Medicine in a North Norwegian Community - Kiil, Mona Anita; Salamonsen, Anita (Academic Journal of Interdisciplinary Studies, 2013)
Scandinavian welfare states like Norway represent a cultural context in which citizens who become ill are supposed to trust and receive health care within the conventional health care system that is officially subsidized and based on biomedical knowledge. Despite this officially initiated health practice, unofficial and non-commercial health practices exist in many North Norwegian communities, consisting of traditional healers which people actively use or would consider to use when facing illness or crisis. The municipality of Nordreisa in Northern Troms is commonly described as ”where the three tribes meet”- the “tribes” being the indigenous Sami people, the Kven, descendants of Finnish immigrants, and the majority population of the Norwegians - and for this reason the region has historically been considered a cultural melting pot. The eight participants in this ethnographic study, recruited from an outpatient mental health care clinic in Nordreisa, find themselves positioned as users of both traditional healing practices and the conventional mental health care offered by the clinic. The aim of this article is to explore mental ill patients’ reasons for, and experiences from, the use of traditional healing as well as the conventional health care system within this cultural context by applying theories of trust and embodiment on important empirical patterns of illness behavior. The participants experienced being-and juggling- between the two significantly different medical and cultural systems. In our perspective, these patients’ use of both systems can be understood as “embodied health practices”, based on different cultural approaches to health, healing and knowledge, and thus, barriers of embodied health care practices and trust may cause problems in the encounters between mentally ill patients and their treatment providers. The participants experienced vulnerability and expressed lack of trust in the conventional mental health care in regards to how their traditional healing practices were understood. ...